Formulation, Evaluation and Optimization of Sublingual Tablet of Clonidine Hcl: Pharmaceutical Science-Pharmaceutics for effective drug dosage - Ashok Mahajan; Parmar Jayendra; Priyal Patel; Shailesh Koradiya; Falgun Mehta (International Journal of Life Science and Pharma Research, 2022)
Clonidine hydrochloride (CHL) is a centrally acting alpha two adrenergic agonist. It crosses the blood brain barrier and acts in hypothalamus to induce a decrease in blood pressure. The objective of the present study was to develop and evaluate sublingual tablet of Clonidine Hcl for rapid action and to improve patient compliance to therapy. Wet granulation method was used to prepare sublingual tablet of Clonidine HCL. 32 factorial designs were used to study the effect of binder concentration on dependent variables such as friability disintegration time and wetting time. The prepared formulations were evaluated for various parameters such diameter, thickness, weight variation, hardness, friability, wetting time, drug content, in vitro disintegration time and stability studies Results (Hausner’s ratio 1.24, Carrs index less than 13% and angle of repose 29? ) revealed that all pre compression parameters meet the standard values indicating good flow properties. The average weight, friability and hardness were within compendial limits which showed that all formulations possessed good mechanical strength. The formulation F8 containing 5 % binder and 6 % disintegrant showed minimum disintegration time and wetting time, good friability, drug content and rapid drug release. Prepared sublingual tablets of Clonidine Hcl, were able to provide rapid drug release (94% drug release in 10 minutes) which is a prerequisite for the treatment of hypertension.